2021
DOI: 10.3390/horticulturae7110470
|View full text |Cite
|
Sign up to set email alerts
|

Natural Plant Extracts and Microbial Antagonists to Control Fungal Pathogens and Improve the Productivity of Zucchini (Cucurbita pepo L.) In Vitro and in Greenhouse

Abstract: Background: Natural plant extracts and microbial antagonists have the potential for use in increasing the fungal resistance and productivity of horticulture plants. Methods: The purpose of this study was to evaluate the ability of both natural plant extracts and microbial antagonists as a biotical control of some fungal pathogens, i.e., Fusarium ssp., Exserohilum ssp. and Nigrospora ssp., along with improving the growth and productivity performance of zucchini under greenhouse conditions. Eucalyptus camaldulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 106 publications
1
21
0
Order By: Relevance
“…Plant growth, quality, tolerance to abiotic and biotic stresses, photosynthesis, and using nutrients, fertilizers, and water are able to be enhanced by plant-derived biostimulants (PDBs) by modulating plant biochemical, molecular, and physiological processes (Rouphael and Colla, 2020b ; Godlewska et al, 2021 ; Mosa et al, 2021b ). Our previous work (Hassan et al, 2021 ) showed that the most abundant phenolic compounds in Eucalyptus camaldulensis LE were pyrogallol, caffeic acid, and p -coumaric acid, in Citrus sinensis LE were syringic and ferulic acids, and in Ficus benghalensis were gallic, p-coumaric, and syringic acids.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Plant growth, quality, tolerance to abiotic and biotic stresses, photosynthesis, and using nutrients, fertilizers, and water are able to be enhanced by plant-derived biostimulants (PDBs) by modulating plant biochemical, molecular, and physiological processes (Rouphael and Colla, 2020b ; Godlewska et al, 2021 ; Mosa et al, 2021b ). Our previous work (Hassan et al, 2021 ) showed that the most abundant phenolic compounds in Eucalyptus camaldulensis LE were pyrogallol, caffeic acid, and p -coumaric acid, in Citrus sinensis LE were syringic and ferulic acids, and in Ficus benghalensis were gallic, p-coumaric, and syringic acids.…”
Section: Discussionmentioning
confidence: 96%
“…It can be said that biological stimulants have a positive effect on a number of chemical properties of fruits and vegetables. It is evident that the use of several types of PDBs has potential effects on the development and quality of several plant species, for example, tomato (Souri and Bakhtiarizade, 2019 ), rocket (Di Mola et al, 2019 ), and zucchini (Hassan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatograms were obtained and analyzed using the Agilent ChemStation. The separation and identification conditions ca be found in the previous work 58 .…”
Section: Methodsmentioning
confidence: 99%